OBESITY ASSOCIATED ATRIAL FIBRILLATION: EPICARDIAL FAT TISSUE IN ETIOPATHOGENESIS - M. A. Druzhilov; T. Yu. Kuznetsova (Российский кардиологический журнал)
The established relationship in obesity and atrial fibrillation comorbidity, under the context of raising prevalence of both disorders, determines the search for new ways of underlying pathogenetic mechanisms. Nowadays, quite an amount of evidence has been collected, on the existence of relationships between ectopic visceral adipose tissue of the heart and atrial fibrillation. The article focuses on the role of epicardial adipose tissue in development and progression of atrial fibrillation, discussing possible pathogenetic chains of such association and potential clinical significance